Proceedings of the 15th International Conference on World Wide Web 2006
DOI: 10.1145/1135777.1135839
|View full text |Cite
|
Sign up to set email alerts
|

Exploring social annotations for the semantic web

Abstract: In order to obtain a machine understandable semantics for web resources, research on the Semantic Web tries to annotate web resources with concepts and relations from explicitly defined formal ontologies. This kind of formal annotation is usually done manually or semi-automatically. In this paper, we explore a complement approach that focuses on the "social annotations of the web" which are annotations manually made by normal web users without a predefined formal ontology. Compared to the formal annotations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
171
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(180 citation statements)
references
References 28 publications
1
171
0
8
Order By: Relevance
“…Aquest coneixement reflecteix les opinions independents i diverses d'un grup de persones (Sunstein 2006). Les etiquetes d'aquesta folksonomy (Angeletou et al 2007) estan sovint força relacionades entre si, ja que poden ser utilitzades per un usuari per etiquetar recursos relacionats, o per diferents usuaris per etiquetar el mateix recurs (Wu, Zhang, and Yu 2006;Campbell 2006). Els patrons que sorgeixen d'aquestes pràctiques d'etiquetatge proporcionen, no només una manera d'organitzar la informació per als usuaris (Kipp and Campbell 2006), sinó també una capa de semàntica feble (Dye 2006) …”
Section: Feina Relacionadaunclassified
“…Aquest coneixement reflecteix les opinions independents i diverses d'un grup de persones (Sunstein 2006). Les etiquetes d'aquesta folksonomy (Angeletou et al 2007) estan sovint força relacionades entre si, ja que poden ser utilitzades per un usuari per etiquetar recursos relacionats, o per diferents usuaris per etiquetar el mateix recurs (Wu, Zhang, and Yu 2006;Campbell 2006). Els patrons que sorgeixen d'aquestes pràctiques d'etiquetatge proporcionen, no només una manera d'organitzar la informació per als usuaris (Kipp and Campbell 2006), sinó també una capa de semàntica feble (Dye 2006) …”
Section: Feina Relacionadaunclassified
“…Another piece of work that is related to ours is introduced in [30]. This work applies a separable mixture model to demonstrate emergent semantics in a social tagging system.…”
Section: Related Workmentioning
confidence: 99%
“…One of such approach is to build emergent semantics from social web which aims to overcome the knowledge acquisition bottleneck. In [14] and [27], it has been shown that light weight ontologies can be constructed from the social tagging behaviors.…”
Section: Related Workmentioning
confidence: 99%